Respuesta :

Answer:

1.8 x [tex]10^{13}[/tex]

Step-by-step explanation:

( 9 x 10²) (2 x [tex]10^{10}[/tex] )

= (9)(2) x  [tex]10^{10+2}[/tex]

=18 x [tex]10^{12}[/tex]

= 1.8 x [tex]10^{13}[/tex]

Answer:

(9x10^2)(2x10^10)

= 1.9 x 10^13 (In scientific notation)

Step-by-step explanation:

Expression to be simplified is given as:

(9x10^2)(2x10^10)

= 9x10^2x2x10^10

= 9x2x10^2x10^10

The base here in the expression is same so the power will add up:

= 18 x 10^(2+10)

= 1.8 x 10^12

Using Scientific notation on the expression, we know that the decimal point must after the first digit so that the number let us say x is such that x > 0 and x < 10. To move decimal one place back, we will multiply it with 10^1:

18 x 10^12

= 1.8 x 10 x 10^12

= 1.8 x 10^(1+12)

= 1.8 x 10^13

ACCESS MORE